Assessment of psychophysiological indicators of e-sports players, winners of the international e-sports festival «Battle for science» 2023 - Shuvalova L.S. ,; Grebenkov V.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the psychophysiological indicators characterizing the properties of attention and cognitive processes of the winners of the Battle for Science - 2023 festival in the disciplines "Caliber", "League of Legends" and "DOTA 2". Methods and structure of the study. To collect data, standardized methods were used to assess psychophysiological indicators characterizing concentration, stability of concentration, and speed of information processing. Additionally, operational and combinatorial abilities were assessed; ability to analyze and synthesize. Results and conclusions. The results of a study of the psychophysiological indicators of the winners of the international e-sports festival “Battle for Science” 2023 are presented. The need for prospective studies of the psychophysiological indicators of e-sportsmen competing in selected disciplines is determined.